The effect of social rank on milking and feeding behaviour in automatic milking system for dairy cows - Danielsson, Tina (SLU/Dept. of Animal Nutrition and Management (until 231231), 2012)
Today automatic milking systems (AMS) are growing in popularity. In these systems the cows are loose and have to get to the robot and the feed on their own. The cows ranking in this system affect their welfare. In this study data from seven years in an AMS was used and analysed. The aim was to investigate how ranking could affect the behaviour of the cows at milking and at feeding. It was seen that high ranking cows had significant difference in the shape of their lactation curve compared to the low ranked cows. And it was also seen that the high ranked cows were milking more. This might be explained by the high ranking cows eating more often, but they were not eating more in total. Further the difference in lactation curve could be explained by a shorter milking interval for the high ranking cows. These factors do not only affect the production but also the welfare of the low ranking cows due to long milking interval etc. Finding these low ranking cows is essential for being able to improve their welfare. In this study it was found that a low ranked cow might not stay low ranked the entire time in the stable, 62% of all cows had a rise in DV during lactation.